The Metaphor between al-Rumani and Sayyid Qutb in the Holy Qur’an as a model: a comparative study - Ku Nurfadhmah Syahadah Ku Ahmad Puzi; Nadwah Haji Daud (Studia Quranika, 2024)
This study, Metaphor between Al-Rumani and Sayyid Qutb in the Holy Qur'an: A Comparative Study, compared Sayyid Qutb, a well-known modern writer, with Al-Rumani, an older writer, in order to emphasize the metaphor technique. The study's approach will be twofold: first, it will define the terms "statement" and "metaphor," and then it will adopt an analytical approach by analyzing the metaphor used in the Holy Quran by Al-Ramani and Sayyid Qutb. The study's conclusions and their differences indicate that these two scholars agree that rhetoric—and metaphor in particular—is a crucial component of miracles in the Holy Qur'an. They use various methods and passages from the Holy Qur'an to explain metaphors in different ways